Opowieść transmedialna – znak naszych czasów - Boczkowska, Magdalena (Postscriptum Polonistyczne, 2020)
The article presents the socalled transmedia stories that have become more popular in the epoch of media convergence. Transmedia texts are the texts that tell their stories using different media, for example television, Internet or literature. Transmediality can be regarded as a kind of intertextuality. The author also presents several novels whose plot as well as other elements (for example fictive author) refer to popular TV series.